Cain's Kin and Abel's Blood: Beowulf 1361-4 - Michael Bintley (Opticon1826, 2010)
Amongst the various texts which are thought to have influenced the depiction of Grendel’s mere in Beowulf, the possibility has not yet been considered that the poet also drew upon a tradition associated with Grendel’s descent from Cain, also to be found in the composite Genesis poem of the Junius manuscript (Oxford, Bodleian Library MS Junius 11, SC 5123), and Aldhelm’s Carmen de virginitate. This connection only becomes apparent upon closer examination of the woodland grove overhanging the refuge in Grendel’s fens. Of the many trees that appear in Old English literature, few can be as sinister as these.